Realisation of a multi-sensor framework for process monitoring of the wire arc additive manufacturing in producing Ti-6Al-4V parts. Issue 8 (3rd August 2018) - Xu, Fangda; Dhokia, Vimal; Colegrove, Paul; McAndrew, Anthony; Williams, Stewart; Henstridge, Andrew; Newman, Stephen T.
ABSTRACT: Wire arc additive manufacturing (WAAM) is arc welding-based additive manufacture which is providing a major opportunity for the aerospace industry to reduce buy-to-fly ratios from 20:1 with forging and machining to 5:1 with WAAM. The WAAM method can build a wide range of near net shapes from a variety of high-grade (metallic) materials at high deposition speeds without the need for costly moulds. However, current WAAM methods and technologies are unable to produce parts reliably and with consistent structural material properties and required dimensional accuracy. This is due to the complexity of the process and the lack of process control strategies. This article makes a brief review on monitoring methods that have been used in WAAM or similar processes. The authors then identify the requirements for a WAAM monitoring system based on the common attributes of the process. Finally, a novel multi-sensor framework is realised which monitors the system voltage/current, part profile and environmental oxygen level. The authors provide a new signal process technique to acquire accurate voltage and current signal without random noises thereby significantly improving the quality of WAAM manufacturing.